The effects of aerobic exercise in water on perceived pain and heart rate variability in women with fibromyalgia Efectos del ejercicio aeróbico en agua sobre el dolor percibido y la variabilidad cardiaca en mujeres con fibromialgia - Riquelme, Matías M.; Melipillán, Claudia A.; Bacon, Alexis A.; Niño-Méndez, Oscar A.; Nuñez Espinosa, Cristian Andrés (My University, 2021)
Fibromyalgia is a disease characterized by conical pain associated with autonomic dysregulation of the sufferer, without many treatment alternatives. The objective of this study was to find out the relationship between physical exercise in an aquatic environment, pain perception and cardiovascular autonomic control in adult women suffering from fibromyalgia. The sample consisted of 15 women diagnosed with fibromyalgia who participated in 24 40-minute exercise sessions in a water environment. Anthropometric measures, heart rate variability (HRV) and pain perception (PCS) were evaluated in four experimental times (t1, baseline; t2, session 8; t3, session 16; t4, session 24). In addition, the perception of pain was evaluated in each session through VAS. The results show that the perception of pain through VAS decreased when comparing all the means evaluated before and after each session (p <0.05). In the PCS application, a lower Total Pain and Rumination was obtained when comparing t1 with t4. HRV values showed that SDNN and RMSSD were higher after the session, when t4 was compared with t1 (p <0.05). The mean heart rate decreased at the end of the sessions, showing a better adaptation to exercise. The relationship between pain and cardiac measurements was given by a positive correlation in the pain domains recorded before the sessions and the RMSSD and SDNN values. In conclusion, the practice of physical exercise in an aquatic environment would indicate a lower perception of pain and a better cardiac autonomic response in women with fibromyalgia.
Keywords: autonomous nervous system; exercise; fibromyalgia; pain